Late acne in women: patients of gynecologists, endocrinologists or dermatologists? - Igor Yu. Golousenko (Consilium Medicum, 2021)
The article raises the problem of late acne in women. As a result of observation of 326 patients aged 20 to 40 years, evaluation of the data of a significant number of laboratory and instrumental tests, it was found that 257 (79%) women had hyperandrogenism of various etiologies. On the basis of which, 6 groups of patients were identified, which allows applying etiological treatment. It is concluded that only the cooperation of dermatovenerologists, gynecologists, endocrinologists can help an increasing number of such patients.